Effects of a proprioceptive focal stimulation (Equistasi®) on reducing the biomechanical risk factors associated with ACL injury in female footballers - Spolaor, F.; Guiotto, A.; Ciniglio, A.; Cibin, F.; Sawacha, Z. (Frontiers in Sports and Active Living, 2023)
Introduction: Football presents a high rate of lower limb injuries and high incidence of Anterior Cruciate Ligament (ACL) rupture, especially in women. Due to this there is the need to optimize current prevention programs. This study aims to verify the possibility to reduce the biomechanical risk factors associated with ACL injury, through the application of proprioceptive stimulation by means of the Equistasi® device.